A CROSS-LAYER OPPORTUNISTIC MAC/ROUTING PROTOCOL FOR RELIABLE COMMUNICATION IN WIRELESS BODY AREA NETWORKS - ABBASI, UMER FIAZ (2015)
Recent innovations in sensor design and communication systems have enabled a new sub-category of wireless networks which is known as Wireless Body Area Network (WBAN). WBAN is a network of wearable sensor nodes that sense physiological signals of a body. The development of protocols for WBAN is facing several challenges due to body shadowing, heterogeneous nature, environmental interference, limited energy resources, low transmission power and less number of nodes. Loss of packets becomes a major challenge in WBAN because it may severely affect the monitoring of a patient, especially when vital signs are being monitored. Numerous routing, Media Access Control (MAC) and cross-layer techniques solve many issues in wireless networks that also exist in WBAN. However, these techniques are not suitable for WBAN due to its unique characteristics. Currently, the development ofMAC and routing protocols for WBAN is limited.